Cataract surgical services in Madagascar - Ndaule, Eric (Department of Public Health and Family Medicine, 2019)
Objective: The main purpose of this study was to evaluate cataract surgical services in Madagascar to help guide the national eye health program. Methods: A retrospective study that used cataract surgical data collected between January 1st and December 31st, 2012 in 8 regional capitals (districts) of Madagascar. 1072 cataract operated eyes from 8 regional capitals supported by Kilimanjaro Centre for Community Ophthalmology (KCCO) satellite centers were analysed. Results: The study findings demonstrated a borderline post-operative visual acuity outcome after 24 hours but showed visual improvements 4 weeks after follow up. Males were more likely to have cataract surgeries compared to females. The cataract surgery rate (CSR) was 1467 in 8 regional capitals of Madagascar. Conclusion: This study demonstrated unequal distribution of cataract surgical services in Madagascar. Therefore, the findings of this study could be used to advocate for equitable provision of cataract surgery across all regions in Madagascar.